The effect of temperature and drought stress on Bambara groundnut (Vigna subterranea (L.) Verdc) landraces - Alshareef, Ibraheem (2011)
Five experiments were conducted to investigate the effect of drought and high temperature stress on the growth and development of bambara groundnut (Vigna subterranea (L.) Verdc). Three glasshouse experiments were conducted at the University of Nottingham, Sutton Bonington Campus, UK, and two field experiments were conducted at the Botswana College of Agriculture, Gaborone, Botswana. In the glasshouse experiments, two landraces were grown, S19-3 (from hot, dry environment/ Namibia) and Uniswa Red (from cool, wet environment/ Swaziland) under two different temperatures, 33±5 oC and 23±5 oC. In the first experiment (2006), soil moisture was non-limiting. In the second experiment (2007) drought was imposed at pod filling stage (77 DAS). In the third experiment (2008), the same two landraces were grown under the same temperatures, but the drought was imposed at flowering (30 DAS). In the first field experiment, two landraces were grown under three sowing dates and two water regimes; rain fed and drought. The two landraces were Dip C (from hot, dry environment/ Botswana) and Uniswa Red. Drought was imposed approximately at pod filling (63 DAS). In the second field experiment, the same landraces were grown under the same sowing dates and water regimes with drought imposed at 30 DAS.